2018
DOI: 10.21916/mlr.2018.8
|View full text |Cite
|
Sign up to set email alerts
|

Who chooses part-time work and why?

Abstract: The Federal Interagency Forum on Aging-Related Statistics (Forum) was founded in 1986 to foster collaboration among Federal agencies that produce or use statistical data on the older population. Forum agencies as of June 2016 are listed below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
(22 reference statements)
0
20
0
1
Order By: Relevance
“…Note that the unemployment rate was well above the underemployment rate before the Great Recession. For the US, our underemployment index is not available, and we have to proxy it using U7, a statistic which only uses data on involuntary part-timers who are usually part-time (see Dunn, 2018). However, from the UK as well as data from other European countries based on the European Labour Force Surveys, it is clear that it is not just involuntary part-timers who want more hours, but so too do voluntary part-timers and even some fulltimers (Bell and Blanchflower, 2019).…”
Section: Unemployment and Underemploymentmentioning
confidence: 99%
“…Note that the unemployment rate was well above the underemployment rate before the Great Recession. For the US, our underemployment index is not available, and we have to proxy it using U7, a statistic which only uses data on involuntary part-timers who are usually part-time (see Dunn, 2018). However, from the UK as well as data from other European countries based on the European Labour Force Surveys, it is clear that it is not just involuntary part-timers who want more hours, but so too do voluntary part-timers and even some fulltimers (Bell and Blanchflower, 2019).…”
Section: Unemployment and Underemploymentmentioning
confidence: 99%
“…By age, teenagers and older workers are most likely to work part-time compared with prime-age (25-54 years) workers. Older workers (65 years of age and older) have tended to work part-time a great deal more than workers age 55 to 64 years, but their employment in part-time work has declined greatly from 1994 to 2016, from 48.3% to 34.6% ( Dunn, 2018 ). Nevertheless, many older workers need assistance in searching for part-time work, something that the unemployment insurance (UI) system has rarely supported in the past when recipients formerly had been working full-time.…”
Section: Part-time Employmentmentioning
confidence: 99%
“…It has been over 50 years since the passage of the Equal Pay Act in 1963, yet women only make 80 cents for every dollar that a man earns (Fontenot, Semega, & Kollar, ). Societal explanations for this pay gap between men and women include higher rates and success of negotiation attempts for males, a disproportionately higher rate of males in leadership positions, and higher rates of females working part‐time and/or shouldering a greater proportion of family care requirements (Artz, Goodall, & Oswald, ; Bowles, Babcock, & Lai, ; Budig & England, ; Dunn, ; Hultin, ; McKinsey & Company, ). The degree to which the aforementioned factors contribute to the pay gap in genetic counseling has not been specifically explored.…”
Section: Introductionmentioning
confidence: 99%
“…Female genetic counselors may also be at a salary disadvantage due to family care responsibilities that limit their availability to work full‐time or work long hours. Studies of non‐genetic counseling fields have shown that women across the world are almost twice as likely to hold part‐time positions and experience breaks in employment than men (OECD, ) and may experience part‐time work or breaks in employment for reasons relating to child and family care (Budig & England, ; Dunn, ; Juhn & McCue, ). It should be explored if such factors impact salary in genetic counseling settings.…”
Section: Introductionmentioning
confidence: 99%